2010
DOI: 10.1111/j.1753-6405.2010.00469.x
|View full text |Cite|
|
Sign up to set email alerts
|

From hypothetical scenario to tragic reality: A salutary lesson in risk communication and the Victorian 2009 bushfires

Abstract: There is a need in public health risk and emergency situations to focus on community development, information and consultation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Forty papers were found that provided information pertinent to communication and public action during natural disasters. Twenty-one publications relate to the origin and media form, with thirteen providing information on traditional media [9][10][11][12][13][14][15][16][17][18][19][20][21], eleven on nontraditional sources [10,11,15,[20][21][22][23][24][25][26][27], and seven on choice of media [9][10][11]15,18,28,29]. Five articles provided information on smoke avoidance behaviours [19,20,22,25,30,31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty papers were found that provided information pertinent to communication and public action during natural disasters. Twenty-one publications relate to the origin and media form, with thirteen providing information on traditional media [9][10][11][12][13][14][15][16][17][18][19][20][21], eleven on nontraditional sources [10,11,15,[20][21][22][23][24][25][26][27], and seven on choice of media [9][10][11]15,18,28,29]. Five articles provided information on smoke avoidance behaviours [19,20,22,25,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Five articles provided information on smoke avoidance behaviours [19,20,22,25,30,31]. Twenty-nine papers provide advice on message style, with nine relating to message content [9,18,20,22,27,[32][33][34][35], nineteen relating to message style [11,14,15,18,19,21,22,30,[32][33][34][36][37][38][39][40][41][42][43][44], nine relating to the origin of the message [10,14,15,18,21,22,34,38,42,45], and seven specifically mentioning two-way dialogue [15,18,33,36,[46...…”
Section: Resultsmentioning
confidence: 99%
“…We are pleased that the sections in this February 2013 issue reflect their interests and work. Also of note, and to remind us of Delys's work, our cover photograph reflects the challenges of our climate and of climate change, which we covered in a previous editorial 1,2 …”
mentioning
confidence: 97%
“…Also of note, and to remind us of Delys's work, our cover photograph reflects the challenges of our climate and of climate change, which we covered in a previous editorial. 1,2 We are also saying farewell to Jeanne Daly and Sandy Thompson. We thank them for their contributions and will miss their thoughtful contributions as editors.…”
mentioning
confidence: 98%
“…A 2009 Australia brushfire study examining the means of receiving public health messages found that people over 40 years of age preferred government-funded local radio, local papers, and state/council spokesperson and emergency services. In the same study those under 40 years of age preferred television, local papers, and emergency services (Burns, Robinson, and Smith 2010;Fish et al 2017). Both the San Diego and Australian studies demonstrate that the mode of communication is dependent on the community to which it is given.…”
Section: Surveys Public Perceptionsmentioning
confidence: 89%